ANALISIS STRATEGI GURU DALAM MENINGKATKAN PEMAHAMAN KONSEP IPAS SISWA KELAS V SEKOLAH DASAR INPRES KARANGLE - Ariani Indah Lestari Masae; Chintia M.P. Ati; Heryon Bernard Mbuik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Conceptual understanding is one of the primary objectives of Integrated Science and Social Studies (IPAS) learning in elementary schools. However, many students still experience difficulties in understanding concepts comprehensively because classroom instruction is often teacher-centered, resulting in limited student participation. This condition highlights the importance of teachers' instructional strategies in creating meaningful learning experiences that encourage student engagement and connect learning materials with real-life situations. This study aimed to describe teachers' strategies in improving fifth-grade students' conceptual understanding of IPAS at SD Inpres Karangle, particularly on the topic of living organisms' adaptation. This research employed a qualitative descriptive approach. The research participants consisted of the fifth-grade teacher as the main informant, the school principal as a supporting informant, and fifth-grade students as complementary informants. Data were collected through classroom observations, semi-structured interviews, documentation, and document analysis. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured using source and technique triangulation. The findings revealed that the teacher implemented various instructional strategies, including careful lesson planning, the use of diverse teaching methods, active learning activities, effective classroom management, and continuous evaluation accompanied by constructive feedback. These strategies successfully increased students' participation in classroom learning, enabling them to actively discuss, ask questions, observe, and relate learning materials to their daily experiences. Nevertheless, several challenges remained, including limited instructional media, differences in students' learning abilities, and limited instructional time. Therefore, teachers are encouraged to continuously develop innovative and contextual learning strategies to further enhance students' conceptual understanding of IPAS.